Erratum: Characterization of Ready-to-Drink Decaffeinated Coffee Enriched with Lime and Lemon - Nita Kuswardhani; Dania Mazidatul Hana; Andi Eko Wiyono (Department of Agroindustrial Technology, Faculty of Agricultural Technology UGM, 2026)
This Erratum relates to the following article:Kuswardhani, N., Hana, D.M., Wiyono, A.E., 2025. Characterization of Ready-to-Drink Decaffeinated Coffee Enriched with Lime and Lemon. Agroindustrial Journal 12(1), 54–65. https://doi.org/10.22146/aij.v12i1.100954The publisher regrets that, due to a production error, the publication metadata on page 1 of the published PDF version of the article (DOI: 10.22146/aij.v12i1.100954) contained incorrect dates. The incorrect information appeared as: “Received: June-13-2025; Accepted: June-26-2025; Published: June-30-2025”. The correct dates are: “Received: October 23, 2024; Accepted: June 26, 2025; Published: June 30, 2025”.The editorial office regrets the error.